Integration of IBL and CLIL in Preparing Prospective Teachers for Teaching Natural Sciences in Multilingual Environment - Irina M. Babich (National Research Mordova State University, 2021)
Introduction. The relevance of the problem of preparing prospective teachers of natural sciences for teaching in several languages is determined by the social need of society. Insufficient practical training of young specialists requires the search for effective methods to help solve the problem. The aim of the research was to study the impact of the integration of IBL and CLIL methods on the quality of prospective teachers’ preparation to teach science subjects (taking Chemistry as an example) in English. The integration of CLIL and IBL methods is proposed to prepare prospective teachers of natural sciences for teaching in English which serves as a foreign language in a multilingual environment. Materials and Methods.Using the methods of pedagogical experiment, observation, testing, analysis of lesson recordings, descriptive and mathematical statistics, prospective science teachers’ speech acts as indicators of effective training were analyzed during the period of pedagogical apprenticeship. The research was carried out before and after learning in two groups of students studying with application of the CLIL method (control group) and the integration of IBL and CLIL (experimental group). Results. Obtained results demonstrate the non-random pattern of the changes between the two groups of students. Experimental students expressed more directives. A significant increase was observed in high-level questions at the stages of lessons with the organization of independent student research. The types of directive acts have become more diverse than in the control group. The integration of the CLIL and IBL methods had a positive effect on the growth of indicators of the quality of student preparation. Discussion and Conclusion. The presented results can be used to prepare prospective science teachers for teaching subjects in any second language. The results will be relevant for university lecturers in European and CIS countries who are looking for effective ways to train multilingual teachers.